2016
DOI: 10.15361/1984-5529.2016v44n3p446-450
|View full text |Cite
|
Sign up to set email alerts
|

Variability of mass and content of mineral elements in grains of the common bean cultivar Pérola

Abstract: The cultivar Pérola is the most widely bean cultivar cropped. In the market, it is a reference in grain size, which is related to its mass, which, in turn, is influenced by the growing conditions. The objective was to quantify the 100-grain mass and the contents of mineral elements in the common bean cultivar Pérola, coming from the municipality of Cristalina, Goiás. It was selected 18 different areas in the city, under center pivot irrigation, where 86 samples of grains were collected during the crop harvest.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
4
0
1
Order By: Relevance
“…Trešnjevac', 'Zelenčec' and 'Puter'). Obtained total nitrogen values were similar to or slightly higher compared to data reported by Bevilaqua and Antunes (2015), Barros and Prudencio (2016) and Silveira et al (2016)…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Trešnjevac', 'Zelenčec' and 'Puter'). Obtained total nitrogen values were similar to or slightly higher compared to data reported by Bevilaqua and Antunes (2015), Barros and Prudencio (2016) and Silveira et al (2016)…”
Section: Resultssupporting
confidence: 84%
“…Both mentioned landraces are from Andean gene pool which indicates high variability in Mn content among landraces of the same gene pool. Determined values were similar or higher to those reported by other authors (Bevilaqua and Antunes, 2015;Barros and Prudencio, 2016;Silveira et al, 2016), except Moraghan and Grafton (2001) who reported 16-27 mg Mn•kg -1 DW.…”
Section: 5% N Dw Respectivelysupporting
confidence: 88%
See 3 more Smart Citations